Método de colheita e superação de dormência na qualidade fisiológica de sementes de Cassia ferruginea - Martins, Cibele Chalita [UNESP]; Machado, Carla Gomes; Martinelli-Seneme, Adriana; Zucareli, Claudemir (Universidade Estadual de Londrina (UEL), 2012)
The harvesting method of fruits of tree species should be adequate to obtain seeds of maximum physiological quality. When present, the dormancy of Cassia ferruginea seeds is due to seed coat impermeability to water. This research work viewed to find the best methods both for the harvesting and for the breaking of dormancy of seeds of that species. The experiment was conducted during two years. In the first, fruits shed from the mother plant and laying on the ground were picked and their seeds submitted to the following treatments: 1. control, 2. mechanical scarification of the seeds with sandpaper no. 220, 3. hot water for 5 minutes (initial and final temperatures of 82 and 69 degrees C, respectively), 4. hot water for 15 minutes (initial and final temperatures of 82 and 51 degrees C, respectively), 5. chemical scarification with H2SO4 (95%) for 20, 30, 40, 50, 60, 70, and 80 minutes. In the second year, seeds were submitted to treatments 2, 3, and 4 whereas acid scarification was applied for 30, 45, and 60 minutes. The results showed that seeds picked from the ground and those taken directly from the mother plant differ in their response to the dormancy breaking procedure. The results also showed that the seeds picked from the ground are better than those harvested directly from the plant and that, when dormant, the best results are attained when seeds are either submitted to mechanical scarification or chemical scarification with sulfuric acid for periods between 30 and 60 minutes.
Methods for harvesting and breaking the dormancy of Cassia ferruginea seeds
Keywords: Harvesting system; Germination; Hard seed